The quality control of medicines : proceedings of the 35th International Congress of Pharmaceutical Sciences, Dublin 1975 - Deasy, P. B.; Timoney, R. F. (Elsevier, 1976)
The Quality Control of Medicines documents the proceedings of the 35th International Congress of Pharmaceutical Sciences, organized by the Pharmaceutical Society of Ireland on behalf of the Federation Internationale Pharmaceutique, held in Dublin, on 1-5 September 1975. The theme chosen for the Congress was """"the basis for the quality control of medicines"""", because of the importance and relevance of quality control in the production and distribution of medicines at national and international levels. This volume is arranged according to the manner in which the theme of the Congress was dev